High-performance self-compacting concrete with recycled aggregates from the precast industry: durability assessment - Barroqueiro, Tiago (2020)
The main objective of this paper is to provide the industry with a simple and practical way of disposing and recovering recycled waste from precast reinforced concrete elements rejected during the quality control process, while minimizing the consumption of natural resources in the production of concrete and, consequently, significantly reducing the environmental impact of both (construction and demolition waste and extracting natural aggregates). In other words, with this work, the intention is to evaluate the feasibility of producing high-performance self-compacting concrete with a less environmental impact, by replacing natural aggregates (NA) with fine and coarse recycled aggregates resulting from the precast industry, which allows the future use of this type of aggregates in the industrial process without reservations concerning the expected durability performance. To achieve these objectives, six types of self-compacting concrete (SCC) were produced incorporating diferente amounts of recycled aggregates. Six replacement ratios for fine recycled aggregates (FRA) and coarse recycled aggregates (CRA) were considered: (FRA/CRA) 0/0; 25/25; 50/50; 100/100; 0/100 and 100/0%. Six di_erent tests were carried out to characterize both the main concrete transport mechanisms and the main concrete degradation mechanisms, namely: the immersion water absorption test, capillary water absorption test, oxygen permeability test, chloride migration test, electrical resistivity test and carbonation test. The obtained results clearly demonstrate that, despite the negative influence of the inclusion of recycled aggregates, it is still possible to produce high-performance self-compacting concrete with perfectly acceptable durability properties.